2013
DOI: 10.1093/icvts/ivt402
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair versus replacement for moderate-to-severe mitral regurgitation in patients undergoing concomitant aortic valve replacement

Abstract: OBJECTIVES: Whether to repair or replace the mitral valve for patients with significant mitral regurgitation undergoing aortic valve replacement is still controversial. METHODS:From January 1990 to December 2011, a total of 663 patients underwent aortic valve replacement combined with mitral valve surgery. Among these, 253 patients (mean age 55.9 ± 14.5 years, 91 females) with moderate-to-severe mitral regurgitation were enrolled to compare the outcomes between double valve replacement (DVR group, n = 158) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
(15 reference statements)
2
15
0
Order By: Relevance
“…Firstly, bileaflet mechanical aortic valves were implanted in all patients in the current study, which made the incidence of thrombosis, anticoagulation related complications and endocarditis was similar in the two groups. Secondly, the previous study suggested that the outcomes of either mitral valve repair or replacement for moderate-to-severe mitral regurgitation in patients undergoing concomitant aortic valve replacement had no statistical significance in terms of long-term survival and valve-related event rates [18]. The similar in-hospital outcomes could be observed at our institute.…”
Section: Discussionsupporting
confidence: 70%
“…Firstly, bileaflet mechanical aortic valves were implanted in all patients in the current study, which made the incidence of thrombosis, anticoagulation related complications and endocarditis was similar in the two groups. Secondly, the previous study suggested that the outcomes of either mitral valve repair or replacement for moderate-to-severe mitral regurgitation in patients undergoing concomitant aortic valve replacement had no statistical significance in terms of long-term survival and valve-related event rates [18]. The similar in-hospital outcomes could be observed at our institute.…”
Section: Discussionsupporting
confidence: 70%
“…Various prospective and retrospective studies advocate better long-term outcome for patients with mitral valve repair with concomitant aortic valve replacement over double valve replacement. [1][2][3] McGonigle et al in a retrospective analysis confirmed significant benefit in survival postsurgery, following either technique. 4 Postoperative complications like bleeding, reoperations, infective endocarditis, and thromboembolic events have similar incidence among the two surgical techniques.…”
Section: Discussionmentioning
confidence: 94%
“…They included patients with all aetiologies and their study involved multiple operators. Despite these favourable early outcomes, they concluded DVR to be more hazardous than AVR with concomitant mitral valve repair based on long-term survival [ 5 ].…”
Section: Discussionmentioning
confidence: 99%